Gold nanoparticles detection by plants extracts – a review / Noor Jaafar ...[et al.]. - Jaafar, Noor; Ahmed, Dina S.; Alshanon, Ahemd; Al-Saffar, Ali Z.; Yousif, Emad (2018)
Many efforts have been employed for gold nanoparticles (AuNPs) green synthesis by utilizing various plant extracts. Nanotechnology treats with the materials usage and production with nanoscale dimension. Nanoscale dimension provides nanoparticles with large surface area to volume ratio and thus very specific properties. Gold nanoparticles (AuNPs) had been in recent study attribute to its high exciton binding energy, large bandwidth and potential applications such as antifungal, antibacterial, antiinflammatory, wound healing, antioxidant, optic properties and antidiabetic. Attribute to the toxic chemicals large rate and extreme environment used in the chemical and physical production of NPs. This review is overall synthesis study of and applications using for AuNPs green synthesis with various biological sources.